How to Teach Physics and Chemistry? Lessons from Teacher Talk of Two Exemplary Teachers - Kärnä, Pirkko Liisa; Vesterinen, Veli-Matti; Harmoinen, Sari; Aksela, Maija (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
This ethnographical study focused on the practices of two highly effective Finnish comprehensive school science teachers, and especially on the role of teachers’ explanations during classroom interactions. The way teachers explained science and inquiry offered the students a model for explanations. Both teachers focused on explaining ideas and concepts as well guided students on making observations and inferences during inquiry tasks. Through this guidance, teachers supported the development of conceptual understanding about scientific models and theories, as well as understanding about the process of scientific inquiry and the interplay of science, technology and society. Both observed teachers had found an approach, which suited their strengths very well. The other used a method, in which students were more involved in providing the explanations, while the paid a closer attention to the way she explained and clarified ideas and concepts. The approaches of both teachers were based on the mutual respect and trust between the teacher and her students. It enabled the teachers to recognize the educational needs of the students and provide the right guidance at the right time. According to the observations of classroom practice as well as the teachers’ interviews, this mutual respect and trust was perhaps the most crucial factor supporting student engagement and learning.